"Drinking Cultures" in University Residential Colleges: An Australian Case Study of the Role of Alcohol Policy, Management, and Organizational Processes. (March 2017) - Leontini, Rose; Schofield, Toni; Brown, Rebecca; Hepworth, Julie
Young people's heavy alcohol use has been widely linked to their "drinking cultures." Recent scholarly commentary, however, suggests that prevailing conceptualizations of drinking culture, including those in "public health-oriented" research, tend to oversimplify the complexities involved. This article contributes to the conceptual clarification and development of young people's "drinking cultures." We provide a case study of a highly publicized example—that of Australian university residential college students. The case study focuses on the role of residential college policy and management in students' alcohol use, examining how they represent, understand, and address it. Adopting a qualitative approach, we identify and analyze key themes from college policy documents and minimally structured interviews with college management related to students' alcohol use. Our analysis is informed by two key existing works on the subject. The first is a sociological framework theorizing young people's heavy drinking as a "culture of intoxication, " which is embedded in and shaped by broader social forces, especially those linked to a "neoliberal social order." The second draws on findings from a previously published study on student drinking in university residential colleges that identified the significant role of institutional "micro-processes" for shaping alcohol use in university residential colleges. In understanding the specific character of students' drinking in Australian university residential colleges, however, we also draw on sociological—specifically neo-institutionalist—approaches to organizations, proposing that Australian college policy and management related to students' drinking do not operate simply as regulatory influences. Rather, they are organizational processes integral to residential college students' drinking cultures and their making. Accordingly, college alcohol policy and management of students' drinking, as they have prevailed in this Australian context, offer limited opportunities for minimizing harmful drinking.